DIGITAL VISUAL ART AS A SOCIAL INTEGRATOR: (on the example of digital art in Kazakhstan) - B.A., Nurbossynova (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
This article examines the evolving role of digital art as a social integrator, with a particular focus on the digital art scene in Kazakhstan. Art has long sought to create emotional and spiritual balance, mediating between contrasts like past and future, reality and dreams, and internal and external worlds. Today, with the rapid development of technology and globalization, art increasingly engages with digital media to perform its communicative and harmonizing functions. The work of contemporary Kazakh digital artists, such as Danabol Birlesbek and Magnificum, addresses significant social issues, including national identity, domestic violence, and environmental concerns. Through their art, these creators provoke reflection on the rapidly changing society in Kazakhstan. Additionally, the article explores the innovative approaches taken by multimedia exhibitions, such as those at Lumiere-Hall in Almaty. These exhibits merge traditional art with new media, transforming the experience into something more immersive and interactive. For instance, the exhibition Salvador Dali. Cryptography blends recognizable Dali imagery with symbolic and interactive digital elements, requiring viewers to actively interpret the narrative rather than passively observe. The article also highlights the work of Nargis Rakhmanova and other Kazakh artists who use digital art as a bridge between traditional cultural values and contemporary social issues. These artists contribute not only to the development of art but also to public discourse on topics such as gender, identity, and family dynamics. By incorporating modern technology into their practices, Kazakh digital artists play a crucial role in shaping the country's cultural transformation and fostering deeper societal dialogue.